Socio-Emotional Education: Discussing its Implementation Within Chilean Educational Context - Barría-Herrera, Pamela; Améstica-Abarca, José Manuel; Miranda-Jaña, Christian (Revista Saberes Educativos, 2021)
The consequences of recent health, social and political crisis have opened up new challenges for Chilean educational system, such as promoting social and emotional development among students. Within this framework, different models and perspectives regarding socio-emotional education and learning have gained relevance. Nevertheless, implementing these models in Chilean educational contexts requires discussing topics related to i) perspectives that may be adopted on emotions within educational processes, (ii) ways of understanding student’s and teacher’s roles in its implementation, and (iii) our own position upon social and emotional learning as an educational proposal. These elements are discussed in this essay.